Mahaica-Mahaicony-Abary project : socioeconomic change in Guyana - Hoppie, Maurice Reginald (University Microfilms International Ann ArbourUS, 1985)
Reviews the economic history of Guyana focussing on the plantation economy and on the evolution of the rice industry. Discusses the ideology, hopes, and dreams of the Guyanese people and developmental programming and planning since world warii. Describes the demographic and geo-physical setting of the MMA Project. Discusses its funding, progress and problems and draws lessons relating to ideology, independence and dependence, decentralization, and benefits.